Digitalization and the degradation of parental authority among Generation Z in Kampung Timor, Ambon City - Paulus Koritelu; Jeffry Ernest Marten Leiwakabessy; William Bernadus Titing; Suleman Watianan (Digital Theory, Culture & Society, 2026)
This study examines the impact of digitalization on changing power relations within families, focusing on the erosion of parental authority among Generation Z in Kampung Timor, Ambon City. The rapid expansion of the internet, social media, and digital technologies has transformed patterns of family interaction while reshaping the values and behaviors of young people. A qualitative approach was employed, with data collected through in-depth interviews, observations, and document analysis involving both parents and children. The findings reveal that digital spaces have shifted sources of authority from parents to external actors, including social media platforms, influencers, and online communities. As a result, parental control has weakened, interpersonal communication has diminished, and traditional parenting practices have become less effective. The digital literacy gap between parents and children further reinforces young people's dominant position in accessing, interpreting, and producing information. These findings highlight the need to adapt parenting practices by strengthening parents’ digital literacy, fostering dialogical communication, and reinforcing family values. Such efforts are essential to sustaining parental authority while promoting healthy parent–child relationships in an increasingly digital society.